Implementing Lean Six Sigma to overcome the production challenges in an aerospace company. Issue 7 (10th June 2016) - Thomas, A. J.; Francis, M.; Fisher, R.; Byard, P.
Abstract: Lean Six Sigma (LSS) has established itself as one of the key business process improvement strategies available to companies today. With roots based in the single strategies of Lean and Six Sigma, LSS offers a dual strategy towards systematically reducing waste and increasing value whilst resolving Critical to Quality (CTQ) issues that affect consistency and repeatability in a product and process. However, the predominating LSS approach is to employ the DMAIC cycle as the key driver in the implementation process. The authors argue that this reduces the effectiveness of LSS since a systematic lean thinking does not take place through this approach. This paper proposes a new Strategic Lean Six Sigma Framework (SLSSF) that attempts to create a more balanced and integrated approach between the Lean and Six Sigma elements and one that is capable of achieving greater efficiency of production whilst also ensuring variation reduction and CTQ issues are eradicated from the production process. The case study involves the application of the SLSSF in an aerospace manufacturing company. The work highlights the key stages of the framework before closing with an analysis of its effectiveness and the difficulties encountered in its application. When the LSS model was implemented, it achieved significant improvements in business performance. The key improvements were seen as; Build time reduction of 20.5%, improved on-time-in-full delivery to customer by 26.5%, reduced value added time by 5% and reduced Non-value added time by 44.5%. Also, estimated financial savings of over £2 Million are proposed.